The Invisible Burden: A Qualitative Study on the Emotional Well-being of Women Over 30 in Peshawar, Pakistan - Naz, Samina; Tabassum, Nihal (The Indonesian Institute of Science and Technology Research, 2025)
The emotional well-being of women in traditional, patriarchal societies is often shaped by sociocultural pressures that differ significantly from Western contexts. This study explores the unique challenges faced by women over 30 in Peshawar, Pakistan, a city with strong Pashtun cultural norms. Using a qualitative phenomenological approach, in-depth interviews were conducted with 15 unmarried and married women aged 30-38. The findings reveal that the trajectory of psychological distress often begins at birth with a son-preference ideology, leading to restricted educational and career opportunities, limited personal autonomy, and sanctioned social control. A particularly significant finding is the prevalence of emotionally exploitative relationships, where male figures, often presented as friends or potential partners, leverage societal constraints to dominate and emotionally blackmail women, severely impacting their mental health. This control is framed within a discourse of religious and cultural propriety, creating intense internal conflict. The discussion highlights that these pressures systematically violate fundamental rights that are globally recognized, leading to chronic anxiety, depression, and a diminished sense of self-worth. The study concludes that the emotional well-being of these women is not merely a mental health issue but a direct consequence of structural inequality. It implies the need for culturally sensitive mental health interventions and robust policy frameworks that challenge the normative gender biases entrenched in the societal fabric.